Birth control, sex and marriage in Britain 1918-1960 - Fisher, Kate.; Oxford eBooks (Oxford : Oxford University Press, 2006)
This text uncovers the history of gender relations, sexual attitudes, and contraceptive practices that accompanied the dramatic decline in family size in the 20th century. Drawing upon oral history accounts, this analysis places men (rather than their wives) behind the drive for smaller families.
Description based on print version record.
Includes bibliographical references and index.
Keywords: Birth control -- Great Britain -- History -- 20th century; Family size -- Great Britain -- History -- 20th century; Sex role -- Great Britain -- History -- 20th century; Great Britain -- Social conditions -- 20th century; Electronic books